Menghadirkan Pembelajaran Kreatif: Pemberdayaan Guru melalui Model Project-Based Learning di Sekolah Entrepreneur Tahfidz Muamalah Al Qudsiyah - Mustarin, Amirah; Novitasari, Ervi; Indrayani, Indrayani; Rahman, Khaidir; Nurmila, Nurmila (Jurusan Teknik Informatika dan Komputer, 2025)
This community service activity aimed to enhance teachers' understanding at Sekolah Entrepreneur Tahfidz Muamalah Al Qudsiyah regarding the Project-Based Learning (PjBL) model, as an effort to promote more creative, contextual, and student-relevant learning. The learning model and media were designed to facilitate students in entrepreneurial learning activities related to aquaculture, which is an integral part of the school's curriculum. The program was implemented through several stages: preparation, initial evaluation, implementation, and final evaluation. The initial assessment revealed that most teachers had not yet fully understood the concept of PjBL. Through training sessions that included material presentation, discussions, and Q&A, a significant improvement in teachers' comprehension was achieved; all participants (100%) demonstrated a good understanding of the PjBL model by the end of the program. This training effectively equipped teachers with the knowledge and skills necessary to design project-based learning, aligning with the strengthening of the Merdeka Curriculum implementation and the development of 21st-century skills. The project learning activity on tilapia aquaculture using the biofloc system was also carried out through hands-on practice in biofloc media preparation, fish cultivation over three months, and periodic sampling. The program’s success highlights the importance of continuous training and mentoring to support innovative learning practices in schools.